How Pro-Poor is the Selection of Seasonal Migrant Workers from Tonga Under New Zealand's Recognised Seasonal Employer (RSE) Program? - John Gibson; David McKenzie; Halahingano Rohorua (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2008)
Temporary migration programs for unskilled workers are increasingly being proposed as a way to both relieve labour shortages in developed countries and aid development in sending countries without entailing many of the costs associated with permanent migration. New Zealand's new Recognised Seasonal Employer (RSE) program is designed with both these goals in mind, enabling unskilled workers from the Pacific Islands to work in horticulture and viticulture in New Zealand for a period of up to seven months. However, the development impact on a sending country will depend not only on how many workers participate, but also on who participates. This paper uses new survey data from Tonga to examine the process of selecting Tongans to work in the RSE, and to analyze how pro-poor the recruitment process has been to date. We find that the workers recruited come from largely agricultural backgrounds, and have lower average incomes and schooling levels than Tongans not participating in the program. We also compare the characteristics of RSE workers to those of Tongans applying to permanently migrate to New Zealand through the Pacific Access Category, and find the RSE workers to be more rural and less educated. The RSE therefore does seem to have succeeded in creating new opportunities for relatively poor and unskilled Tongans to work in New Zealand.
Keywords: 330